2013
DOI: 10.1074/jbc.m113.451088
|View full text |Cite|
|
Sign up to set email alerts
|

The Amyloid Precursor Protein (APP) Triplicated Gene Impairs Neuronal Precursor Differentiation and Neurite Development through Two Different Domains in the Ts65Dn Mouse Model for Down Syndrome

Abstract: Background: Individuals with Down syndrome suffer from mental retardation due to severe neurogenesis impairment. Results: Normalization of the triplicated gene APP expression restores neuronal maturation and differentiation in trisomic neuronal precursors. Conclusion: APP overproduction contributes to neurogenesis impairment in DS.Significance: APP signaling may be a target for therapeutic approaches aiming to improve brain development in DS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 57 publications
3
43
0
Order By: Relevance
“…In a Ts65Dn mouse model of DS, it was demonstrated that the amyloid precursor protein (APP) triplicated gene impairs proliferation of NPCs from SVZ in the hippocampus [85,86] because high levels of the intracellular domain from APP cleavage by γ-secretase can raise the transcription of Ptch1, which is known to repress Shh pathway [85,86]. ELND006 is an inhibitor of γ-secretase that restores the Shh pathway and fully recovers the impaired neurogenesis in Ts65Dn pups [87].…”
Section: Sonic Hedgehog and Neurogenesis In Neurological Diseasesmentioning
confidence: 99%
“…In a Ts65Dn mouse model of DS, it was demonstrated that the amyloid precursor protein (APP) triplicated gene impairs proliferation of NPCs from SVZ in the hippocampus [85,86] because high levels of the intracellular domain from APP cleavage by γ-secretase can raise the transcription of Ptch1, which is known to repress Shh pathway [85,86]. ELND006 is an inhibitor of γ-secretase that restores the Shh pathway and fully recovers the impaired neurogenesis in Ts65Dn pups [87].…”
Section: Sonic Hedgehog and Neurogenesis In Neurological Diseasesmentioning
confidence: 99%
“…APP affects neural precursor cell proliferation, cell fate, and maturation of neurons, as well as gliogenesis [98, 150]. There are both intracellular and secreted domains of APP that appear to play a role for brain development [151].…”
Section: Amyloid and Tau Pathologymentioning
confidence: 99%
“…This alteration can be ascribed to a cascade of events stemming from amyloid precursor protein (APP) triplication and culminating into overexpression of Patched 1 (Ptch1), the repressor of this pathway (Trazzi et al, 2011, Trazzi et al, 2013). In particular, cleavage of the APP-derived carboxy-terminal fragments (CTFs) by the enzyme gamma-secretase gives origin to the amyloid precursor protein intracellular domain (AICD) and either p3 or beta-amyloid (Abeta).…”
Section: Introductionmentioning
confidence: 99%